Analyzing Lexicons of Movements in Wiranjaya Dance - Ni Putu Puriasih; I Gede Budasi; Putu Eka Dambayana S (JALL (Journal of Applied Linguistics and Literacy), 2023)
Wiranjaya dance belongs to bebancihan dance that has many lexicons to identify. Culturally, there are some lexicons in Wiranjaya dance used normally, but time by time the lexicons are less frequently used while doing the dance practices. This study was designed in the form of a descriptive qualitative method and aimed to find the lexicons and their cultural meaning. The obtained data were collected from observation and interview techniques. The result of the research showed that there were thirty-eight lexicons of movements that exist in Wiranjaya dance, classified into seven types of movements, such as stage movements (4 lexicons), hand movements (8 lexicons), leg movements (9 lexicons), body movements (8 lexicons), head movements (4 lexicons), eye movements (4 lexicons), fan movements (1 lexicon). Both of those lexicons and their cultural meaning were given benefit for the education fields. The dance teachers can easily give information to the foreigners who want to know the costume of Wiranjaya dance. In addition, it will help the students who are interested in learning lexicons and their cultural meaning. In other words, this study can help preserve local languages and avoid language death.Keywords: lexicons, cultural meaning, movement, Wiranjaya dance